Peningkatan Kesadaran Masyarakat dalam Pengelolaan Sampah Melalui Kegiatan Literasi Sampah di Kecamatan Tanjung Morawa B - Muhammad Prasetyo Wibowo; Atika Aini nasution; Zahara Meutia; Amril Amril; Rusli Efendi Damanik (Jurnal Informasi Pengabdian Masyarakat, 2026)
Waste management has become a critical environmental issue in many regions of Indonesia, including Tanjung Morawa B District. Low public awareness about proper waste disposal and sorting leads to pollution and health problems. This community service program aimed to increase public awareness of waste management through waste literacy activities. The program was conducted from March to May 2026, involving 50 households in Tanjung Morawa B District. Methods included socialization, training on waste sorting, composting workshops, and the establishment of waste banks. Data were collected through pre-test and post-test questionnaires, observation, and interviews. Results showed a significant increase in public knowledge and awareness, with average test scores rising from 45.6 to 82.3. Community participation in waste sorting increased by 75%, and a waste bank successfully collected 250 kg of recyclable waste within one month. The program implies that literacy-based interventions effectively change community behavior toward sustainable waste management.